The power to choose: Gender balance of power and intra-household educational spending in India - Christophe Nordman; Smriti Sharma (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
We assess the effect of female bargaining power on the share of educational expenditures in the household budget in India. We augment the collective household model by endogenizing female bargaining power and use a three-stage least squares approach to simultaneously estimate female bargaining power, per capita household expenditure and budget share of education. Our key results are: (i) female bargaining power has a positive and significant effect on the household budget share of educational spending; (ii) this bargaining power is associated positively (negatively) with education spending in urban (rural) areas; (iii) female bargaining power has a uniformly positive effect on educational expenditure of girls in urban areas among all caste groups, but the observed negative association in rural areas appears to be driven by one of the lower caste groups; and (iv) a pro-male bias exists in educational spending for all age groups, with some differentiation by location and caste.
Keywords: D13; C31; J16; I25; 330; collective household model; female bargaining power; gender bias; education; India